(untitled) (Journal of Health Sciences, 2025)
Introduction: Various studies conducted in the past few years have shown a causal relationship between human papillomavirus(HPV) and benign and malignant lesions on the laryngeal mucosa. There are no other studies on the association between HPV and laryngeal lesions in Bosnia and Herzegovina. The aim of the study was to investigate the influence of HPV infection on the development of benign and malignant lesions in the larynx. Methods: Samples for the recommended HPV analysis were taken using cotton swabs from Digene’s Specimen Collection Kit (Sample Collection Kit) from the surface of the affected area of the laryngeal mucosa with a gentle rotational movement through the directoscope. Detection of the presence of HPV in the endolaryngeal swab was performed using Digene’s HPV test-Hybrid Capture II, and results were obtained on a DML 2000 luminometer. Results: In this study, a total of 40 patients were enrolled. Among them, 17 cases (42.5%) presented with benign lesions of the larynx, whereas 23 cases (57.5%) had malignant lesions. Within the group of 17 cases with benign lesions, 5 tested positive for HPV: 2 for high-risk HPV (HR HPV), 2 for low-risk HPV (LR HPV), and 1 for both high-risk and LR HPV. Among the 23 cases with malignant lesions, 11 (47.83%) were HPV positive: 5 for HR HPV, 4 for LR HPV, and 2 for both high-risk and LR HPV. Conclusion: Our findings underscore the noteworthy influence of HPV infection on both benign and malignant changes in the laryngeal mucosa. However, future studies necessitate larger sample sizes and the identification of specific virus types.